2010
DOI: 10.5152/akd.2010.165
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of short-term mortality and morbidity after the complete repair of tetralogy of Fallot in infant groups under 12 months and one-four years of age

Abstract: Fallot tetralojili on iki ay altı infantlar ile bir-dört yaş arası çocuk hasta gruplarında tam düzeltme ameliyatı sonrasında kısa dönem mortalite ve morbiditenin belirleyicileriDeterminants of short-term mortality and morbidity after the complete repair of tetralogy of Fallot in infant groups under 12 months and one-four years of age Özgün Araşt›rma Original Investigation 544Yaz›şma Adresi/Address ABSTRACTObjective: In patients with tetralogy of Fallot, infants less than 12 months old and children between one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
3
1
Order By: Relevance
“…The mortality in pediatric age group is comparable to other developing countries, 5.7-14.2% but, it is still higher than the standards worldwide. 18,19 The mean Cardiopulmonary Bypass time and Aortic Cross Clamp time recorded in our study were 94.84±37.92 minutes and 67.17±31.86 minutes respectively which, as compared to a study by Egbe and colleagues, is comparatively higher. 17 Our mean CICU stay managed to be shorter as compared to studies by Hirsh et al who reported an average stay of 9±8 days, Kolcz and Pizarro reporting mean ICU stay of 7 days, and Tamesberger et al presented the average stay to be 6 days.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The mortality in pediatric age group is comparable to other developing countries, 5.7-14.2% but, it is still higher than the standards worldwide. 18,19 The mean Cardiopulmonary Bypass time and Aortic Cross Clamp time recorded in our study were 94.84±37.92 minutes and 67.17±31.86 minutes respectively which, as compared to a study by Egbe and colleagues, is comparatively higher. 17 Our mean CICU stay managed to be shorter as compared to studies by Hirsh et al who reported an average stay of 9±8 days, Kolcz and Pizarro reporting mean ICU stay of 7 days, and Tamesberger et al presented the average stay to be 6 days.…”
Section: Discussioncontrasting
confidence: 68%
“…16,17 In developing countries however, the mortality rate for surgical repair of TOF in infants is 28-70 times higher than the developed countries because late surgical repair of TOF is a common practice in these countries. 18,19 The risk of complications such as suboptimal pulmonary vasculature development, pulmonary artery distortion, diastolic dysfunction, pulmonary vascular disease, end-organ dysfunction and right ventricular hypertrophy have increased due to twostaged operations for TOF. Later in life these sequelae can lead to life threatening arrythmias and even death.…”
Section: Discussionmentioning
confidence: 99%
“…18 However, in a study of 52 patients by Sasmazel et al, no significant correlation was found between the McGoon index and perioperative mortality. 9 We also found that mortality had no significant correlation with the pulmonary annulus and peripheral This article is protected by copyright. All rights reserved.…”
Section: Discussionmentioning
confidence: 59%
“…In developed countries, primary surgical correction is usually done between the age of three to 12 months but due to a variety of factors, including delay in diagnosis, financial limitations, higher morbidity, and mortality due to lack of medical skills in underdeveloped countries, this is not a usual practice. Hence, accurate data on the morbidity and mortality of surgically corrected TOF cases are currently scarce in our countries [ 23 ].…”
Section: Discussionmentioning
confidence: 99%